2010
DOI: 10.1063/1.3380842
|View full text |Cite
|
Sign up to set email alerts
|

Heat fluctuations and phonon hydrodynamics in nanowires

Abstract: We evaluate the second moments of the fluctuations of the total longitudinal heat flux in cylindrical nanowires described by phonon hydrodynamics with boundary conditions accounting for phonon boundary collisions. It is found that the second moments exhibit an explicit dependence on the boundary conditions and, therefore, may provide a suitable tool for analyzing phonon boundary collisions. Furthermore, an analogous dependence is also manifested in the relative probability of forward and backward fluctuations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…However, the experiments indicated that the effective thermal conductivity is approximately linear to the characteristic size rather than the square of size. It is thereby further elucidated that the boundary velocity slip would happen in case of large Kn [29,31]. By introducing the slip boundary condition into the governing equation, the linear size-dependent effective thermal conductivity can be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the experiments indicated that the effective thermal conductivity is approximately linear to the characteristic size rather than the square of size. It is thereby further elucidated that the boundary velocity slip would happen in case of large Kn [29,31]. By introducing the slip boundary condition into the governing equation, the linear size-dependent effective thermal conductivity can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The phonon hydrodynamics [26][27][28][29][30][31] is another pathway to model the nanoscale heat conduction. It originates from the solving of linearized Boltzmann equation.…”
Section: Introductionmentioning
confidence: 99%
“…the heat conduction of nanowires was investigated in [24,25,27,28]. They proposed that the phonon flow exhibits a similar behaviour as rarefied gas flows or microscale flows in microchannels with the rarefied effect.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that the phonon flow exhibits a similar behaviour as rarefied gas flows or microscale flows in microchannels with the rarefied effect. As the velocity on the walls of microchannels satisfies the slip boundary condition, analogously the slip boundary condition of heat flux for the phonon flow in nanowires was assumed in [24,25,27,28]. However, the legitimacy of this slip boundary condition of heat flux on the boundary surface of nanowires needs to be proved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation